Evaluation of serum sex hormones and CD4+ count among HIV patients on HAART, HAART naive patients and apparently healthy subjects in Sokoto, Nigeria - Yelwa, Armiya’u Ahmed; Mainasara, Abdallah Suleiman; Akuyam, Shehu Abubakar; Adamu, Balarabe Isah; Umar, Zayyanu Usman; Abubakar, Sharafudeen Dahiru; Muhammad, Yahaya; Gamde, Solomon Matthias; Abdulazziz, Aisha (International Journal of Research in Medical Sciences, 2020)
Background: Acquired Immunodeficiency Syndrome (AIDS) is a chronic disease associated with Human Immunodeficiency Virus (HIV) which progressively induces depletion of CD4+ T cells, and increased vulnerability to opportunistic infections. Previous reported studies associated HIV-infected men with sexual dysfunction; hypogonadism is the most common endocrinological disorders. Its prevalence remains poorly defined and widely ranging from different studies. Methods: This study evaluated a total of 135 serum sex hormones (testosterone, estrogen, follicle stimulating hormone and luteinizing hormone) and its correlation with CD4+ counts among HIV patients on HAART, HAART naïve patients and negative control subjects (n=45). CD4+ cell counts were estimated using standard flow cytometry method and serum sex hormones by competitive enzyme immunoassay technique. Results: There were significantly lower testosterone and CD4+ levels (p<0.05) among HIV positive HAART naïve men compared to negative control. LH and FSH indicated significant increased (p<0.05) among HIV positive men on HAART. Conclusions: Antiretroviral therapy improves sexual functions in males infected with human immunodeficiency virus. Hence, further study to evaluate its effects on other sexual behaviors.